Talkin’ ‘bout a Negotiation: (Un)Transparent Rapporteurs’ Speeches in the European Parliament - Damien Pennetreau (Politics and Governance, 2021)
For policies to be legitimate, both the policy process and the underlying reasons must be transparent to the public. In the EU, the lion’s share of legislation is nowadays negotiated in informal secluded meeting called trilogues. Therefore, presentation of the trilogues compromise by the rapporteur to the European Parliament (EP) plenary is, arguably, one of the few formal occasions for ‘transparency in process,’ i.e., public access to the details of actual interactions between policymakers. The aim of this article is thus to examine the extent to which rapporteurs are transparent about trilogue negotiations when presenting legislative compromises to the EP during plenary sessions, and to assess whether the extent of transparency is linked to the extent of conflict between legislative actors and to elements of the political context related to rapporteurs. To this purpose, we coded 176 rapporteur speeches and, on this basis, concluded that these speeches poorly discuss the trilogue negotiations. Interinstitutional negotiations are discussed in only 64% of cases, and even when they are, the extent of information about trilogues is generally small. While we do not find support for an effect of political conflicts, some characteristics linked with rapporteurs are significantly related to transparency in process of their speeches. This is the case for their political affiliation and their national culture of transparence.